SISTEM INFORMASI KENAIKAN PANGKAT PEGAWAI DI LINGKUNGAN PEGAWAI NEGERI SIPIL KOTA DENPASAR - A.A Raka Novi Aristi; Made Sudarma; I Made Arsa Suyadnya (Program Studi Teknik Elektro UNUD, 2020)
BKD Denpasar has an employee management information system. The system is useful for managing employees from managing new employees to managing retired employees. The current problem is the system cannot manage staff promotions. The current system is that employees submit promotions by filling in the files manually. The solution proposed in this problem is a promotion information system with existing data and managed using an existing staffing system. The system is designed using a data flow diagram while the database is designed using an entity relationship diagram. Web-based system is built using the PHP programming language. The database is implemented using MySQL. Based on the results of application testing with Black-box testing, all the functionality of the Information system of promotion in the Civil Service Environment Denpasar that has been built can run well. The resulting system can help the performance of administrative officers for promotion. The system built can run well according to user needs.